Bimbingan Teknis Wirausaha Coran Aluminium Bekas untuk Spesimen Uji Tarik - Hadi, Syamsul; Gumono, Gumono; Murdani, Anggit; Hakim, Arif Rahman; Udianto, Pondi (LPPM UNINUS, 2025)
Scrap of Aluminium is not always could be used as a raw material in casting of tensile test specimen, it’s because of shrinkage problem to the mould. The objective of casting trial is to find out the suitable raw material shrinkage of Aluminium casting. The method of the casting trial is to design and manufacture of casting moulds according to the standard of specimen dimension of ASTM E8/E8M-08 for rectangular cross section of gauge length, selection of Aluminium scrap, trial of Aluminium casting, evaluation of tensile test specimen, moulds modification, and evaluation of cast results. The result of casting trial of tensile test specimen was shown that the failure specimen if used Aluminium scrap of 7.99% shrinkage (>6%) and succeed specimen if used Aluminium scrap of 5.71 and 5.32% shrinkages (<6%) which is ready for finishing of the gauge length.